Handbook of Social Movements Across Disciplines - Roggeband, Conny; Klandermans, Bert (Springer International Publishing : Imprint: Springer, 2017)
This handbook provides a broad and comprehensive overview of the study of social movements and collective action, discussing the different disciplinary approaches that have developed. In addition to updated discussions of topics that were included in the 1st edition, this handbook includes substantial advances in the research and scholarship in the field. The study of collective behavior and contentious politics has spread to a number of new disciplines such as communication science, organization science and law. The international wave of new protests in 2013 spurred new scholarship as well. This revised and updated edition integrates the wealth of new theoretical insights and empirical work since 2007.
Keywords: Social sciences.; Anthropology.; Social structure.; Social inequality.; Human geography.; Economic development.; Social change.; elektronické knihy; electronic books